Infographic: Avoiding Monotony in Presenting Teaching Materials - Erny Wahyuni; Thohiriyah Thohiriyah (Universitas Muhammadiyah Semarang, 2018)
Monotony fashion in presenting teaching materials implies the reliance on utilizing one medium to serve the teaching materials. Teachers need to be creative in serving their teaching materials to avoid boredom and monotonousness. Infographic is a versatile tool which can be employed to serve any purposes. In addition, it makes complex information eye-catching. Through its graphic color and animated picture, infographic strengthens the purpose of the lesson taught. Many publishers in 21st-century era reinvent infographic tools to design the infographic. This paper, however, is aimed at reviewing Canva as the infographic tool. Canva provides various themes and professional layouts for creating the compelling infographic to present the teaching materials. In addition, it is a simple tool which is extremely easy to use.